PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM SYARIAH DENGAN INFLASI SEBAGAI VARIABEL MODERASI - Ahmad Muzaqi Mu'min (2023)
An option for people to invest in the capital market, one of which is investing in shares in the Islamic capital market is a very helpful option for Muslims among other capital markets whose financial turnover is not guaranteed in Islamic law. In addition, to guarantee the benefits that will be obtained, an analysis is needed to see how the company's financial performance affects its share price. This study aims to analyze how much influence ROE, EPS, and PER have on Islamic stock prices with inflation as a moderating variable. This research method is quantitative with the financial reports of 6 consumer goods sector companies using a purposive sampling technique for consumer goods sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2012-2021 period. This study uses secondary data collected through the EMIS website, Yahoo Finance, and the Central Bureau of Statistics. The analysis technique uses Panel Data Regression through EViews 10 software. The research findings confirm that ROE and PER have a significant effect on stock prices directly, while EPS does not have a significant effect on stock prices directly. To test inflation as a moderation is not able to moderate the relationship between the ROE, EPS, and PER variables indirectly. The limitations of this study are the lack of references that discuss inflation as a moderating variable with the dependent variable on stock prices, the variables used are still limited to only three independent variables, and financial reports are still limited to the consumer goods sector. For further research it is recommended to use the addition of independent variables other than those used in this study, as well as taking other population and sector samples.